Pengaruh senam hamil terhadap kualitas tidur pada ibu hamil trimester II dan III di Puskesmas Kema Minahasa Utara - Thirsa Mongi (UNIVERSITAS SAM RATULANGI, 2022)
Sleep quality, if not met, will affect the health of the fetus. Pregnant women need about eight hours to sleep at night, besides napping is also needed by pregnant women when entering the second and third trimesters. The more complaints the mother feels so that it interferes with rest at bedtime. One solution to overcome this discomfort is to use the pregnancy exercise method. The purpose of this study was to determine the effect of pregnancy exercise on sleep quality in second and third trimester pregnant women at the Kema Minahasa Public Health Center, North Sumatra. This type of research use a pre-experiment in the form of a one-group Pre-post-test design. The population of this study was pregnant women in the second and third trimester. In the area of the North Kema MInahasa Public Health Center with a total of 16 respondents, the sample Technique used proposive sampling. The results of this study indicate that before the implementation of Pregnancy exercise, 15 pregant women (93,8 %) had poor sleep quality and after the exercise, the quality of sleep in the good category increased to 14 respondents (87,5%). Wilcoxon test results p = 0.000 which means p <0.05, namely Ha is accepted. The conclusion from the results of this study showed thaht was an effect of pregnancy exercise on the quality of sleep pf pregnant women in the second and third trimesters. Suggestions for pregnant women to improve sleep quality by applying the pregnancy exercise method during Pregnancy. Keywords: sleep quality, pregnant women, pregnancy exercise